Co-existence of γ'N phase and γN phase on nitrided austenitic Fe–Cr–Ni alloys- I. experiment. (15th September 2019) - Che, H.L.; Tong, S.; Wang, K.S.; Lei, M.K.; Somers, Marcel A.J.
Abstract: The formation of a metastable and nitrogen-supersaturated f.c.c. interstitial solid solution layer on Fe–Cr–Ni austenitic stainless steel at a moderate temperature around 650–720 K is not entirely understood. In the present work, three groups of austenitic Fe–Cr–Ni alloys, containing systematic variations of chromium, nickel and iron contents were nitrided by plasma-based low-energy ion implantation at 653 K for 4 h and investigated with light-optical microscopy (LOM), electron probe microanalysis (EPMA), (grazing incidence) X-ray diffraction (XRD) and transmission electron microscopy (TEM). Commercial AISI 304L was included for comparison. For the austenitic alloys with a Cr content below 12 wt.%, a duplex layer is observed in the nitrided case where the interface between the top layer, consisting of γ ' -Fe4 N like ordered γ ' N, and the disordered γN (nitrogen enriched austenite) zone underneath is associated with a decrease in N content. For the alloys with a Cr-content over 12 wt.%, a featureless continuous zone is observed with LOM and a gradual decrease in nitrogen content is measured with EPMA. Nevertheless, a similar duplex structure of outer γ ' -Fe4 N like ordered γ ' N and inner γN is confirmed by XRD and TEM for all nitrided alloys, irrespective of the Cr content. The results are discussed in terms of the short-range order (SRO) promoted by the Cr–N interaction and long-range order (LRO) caused by the Fe–N interaction. Graphical abstract: Image 1